Assessment of nutrition status of Turkish elite young male soccer players in the pre-competition period - Ersoy, Nesli; Kalkan, Indrani; Ersoy, Gülgün (Progress in Nutrition, 2019)
Background: Follow up of the nutrition consumption of young soccer players is of great importance not only for their sport performance, but also for the protection of health, physical growth and development. Aim: The objective of this study was to evaluate the nutritional sufficiency status of elite young male athletes in the pre-competition period. Methods: Three-day food consumption and anthropometric measurements of the elite young athletes in the pre-competition period were recorded for 26 male voluntary athletes from a pro-professional soccer team based in Ankara Turkey. Results: The mean height of the athletes were calculated as 175.2Å}6.8 cm, weight 67.3Å}5.9 kg, body mass index (BMI) as 21.9Å}1.3 kg/m2 and body fat percentage 6.2Å}1.7. It was determined that the athletes received an average of 3225Å}692 kcal energy daily whereas their mean energy expenditures per day were 3322Å}240 kcal. The ratios of energy received from carbohydrate, protein and fats were 53.6%, 16.2%, and 30.2%, respectively. Carbohydrate and protein consumption/day/kg body weight were 6.3Å}1.7 g and 1.9Å}0.5 g, respectively. It was determined that vitamin D consumption was inadequate for 92.3% of the athletes and calcium consumption was inadequate for 50% of the athletes. On the other hand, all of the athletes consumed vitamins B2, B6 and B12 as well as phosphorus, iron and zinc above recommended quantities. Conclusions: Nutrient consumption of young athletes at the beginning of their professional life must be monitored by a qualified dietitian and each athlete must have an individual dietary plan. Nutrition education must be arranged and the athletes’ families must be included in these trainings.